C–H Bond Activation and Isoprene Polymerization by Lutetium Alkylaluminate/gallate Complexes Bearing a Peripheral Boryl and a Bulky Hydrotris(pyrazolyl)borate Ligand. Issue 38 (15th September 2017) - Bonath, Martin; Hollfelder, Christoph O.; Schädle, Dorothea; Maichle‐Mössmer, Cäcilia; Sirsch, Peter; Anwander, Reiner
Abstract : The bimetallic lutetium alkylaluminate complex [(Tp t Bu, Me )Lu(Me)(AlMe3 B(NDippCH)2 )] Tp t Bu, Me = hydrotris(3‐Me‐5‐ t Bu‐pyrazolyl)borate formed readily upon addition of 0.5 equivalents of the organoaluminum boryl compound [Me2 AlB(NDippCH)2 ]2 (Dipp = C6 H3 i Pr2 ‐2, 6) to [(Tp t Bu, Me )LuMe2 ] in n ‐hexane solution. Thermally induced cyclometalative C–H bond activation of this compound led to the formation of [(Tp ( t Bu–H)₂/ t Bu, Me )Lu(AlMe2 B(NDippCH)2 )] Tp ( t Bu–H)₂/ t Bu, Me = hydro(3‐Me‐5‐ t Bu‐pyrazolyl)bis[µ‐(3‐Me‐5‐Me2 CCH2 ‐pyrazolyl)]borate in quantitative yields. The latter complex bears an unusual κ 5 coordination mode of the activated tris(pyrazolyl)borate ligand. Additionally, one Lu–CH2 (R) moiety is coordinated by a "neutral" [Me2 AlB(NDippCH)2 ] unit, which can be separated off by addition of THF or trimethylaluminum. The gallium analogue of complex [(Tp t Bu, Me )Lu(Me)(AlMe3 B(NDippCH)2 )] could not be isolated from the respective reaction of monomeric [Me2 GaB(NDippCH)2 ] with [(Tp t Bu, Me )LuMe2 ], but the C–H bond activated gallate complex [(Tp ( t Bu–H)₂/ t Bu, Me )Lu(GaMe2 B(NDippCH)2 )] was obtained instead following a prolonged mild thermal treatment. The performance of the new lutetium complexes as precatalysts in the polymerization of isoprene was assessed and possible activation and deactivation scenarios were studied by NMR spectroscopy. Abstract : The addition compoundA obtained from terminal methyl complex [(Tp t Bu, Me )LuMe2 ] and organoaluminum boryl compound [Me2 AlB(NDippCH)2 ] engages in thermolytic C–H bond activation to afford complexB ; cationizedB (shown to the left asB′ ) polymerizes isoprene, possibly via a Lu–CH2 (R)–Al linkage as the initiating site.